PENERAPAN PENDIDIKAN KARAKTER MELALUI PROGRAM GERAKAN KEPANDUAN HIZBUL WATHAN PADA SEKOLAH DASAR MUHAMMADIYAH VI PALEMBANG - Musni Efendi (Conciencia, 2017)
Each individual is expected to have a character, because someday when an individual gathered in the community, then able to be a good man and who can be proud of. And without realizing each individual has a noble character, starting from leading himself, lead the family, or lead an organization both in the school environment, community environment, and work environment. To reveal the second side, this study formulates the following issues: (1) How to Implement Character Education Through Hizbul wathan Scouting Movement at Primary School Muhammadiyah 6 Palembang? (2) What are the factors that hamper the Implementation of Character Education through Hizbul wathan Scouting Movement at Muhammadiyah Primary School 6 Palembang? To answer that question, this research was designed with the design and implemented in Elementary School Muhammadiyah 6 Palembang. This research uses qualitative field approach that is descriptive qualitative, data collection technique using interview (wawncara) and documentation. Analytical techniques through the data reduction phase, data presentation, and conclusion. The results of the field research have been found (a) Hizbul Wathan's activity at Elementary School Muhammadiyah 6 Palembang has been held since the school was established due to the instruction from Muhammadiyah Central Executive that all schools under Muhammadiyah must perform Hizbul Wathan activities. (B) the implementation of Hizbul Wathan's activities at Muhammadiyah Primary School 6 Palembang is still far from what is expected due to the many obstacles and inhibiting factors (c) in this case with the existence of various obstacles and inhibiting factors of activity hence the purpose of Hizbul Wathan activity to instill the values Leadership is also not running smoothly, but until now the teachers have tried to hold activities in accordance with the planting values of leadership as well as camping activities. To give contribution of school thinking to keep developing and improving its competence in character education implementation through hizbul wathan scouting activity, here arises concept and strategy of constructor in terms of achievement of character education result that effectively and efficient.